Effects of vibrotactile vestibular substitution on vestibular rehabilitation - preliminary study, - Brugnera,Cibele (2015)
ABSTRACT INTRODUCTION: Some patients with severe impairment of body balance do not obtain adequate improvement from vestibular rehabilitation (VR). OBJECTIVE: To evaluate the effectiveness of Vertiguard(tm) biofeedback equipment as a sensory substitution (SS) of the vestibular system in patients who did not obtain sufficient improvement from VR. METHODS: This was a randomized prospective clinical study. Thirteen patients without satisfactory response to conventional VR were randomized into a study group (SG), which received the vibrotactile stimulus from Vertiguard(tm) for ten days, and a control group (CG), which used equipment without the stimulus. For pre- and post-treatment assessment, the Sensory Organization Test (SOT) protocol of the Computerized Dynamic Posturography (CDP) and two scales of balance self-perception, Activities-specific Balance Confidence (ABC) and Dizziness Handicap Inventory (DHI), were used. RESULTS: After treatment, only the SG showed statistically significant improvement in C5 (p = 0.007) and C6 (p = 0.01). On the ABC scale, there was a significant difference in the SG (p= 0.04). The DHI showed a significant difference in CG and SG with regard to the physical aspect, and only in the SG for the functional aspect (p = 0.04). CONCLUSION: The present findings show that sensory substitution using the vibrotactile stimulus of the Vertiguard(tm) system helped with the integration of neural networks involved in maintaining posture, improving the strategies used in the recovery of body balance.